1995
DOI: 10.1039/ja9951000049
|View full text |Cite
|
Sign up to set email alerts
|

Application of palladium- and rhodium-plating of the graphite furnace in electrothermal atomic absorption spectrometry

Abstract: Palladium-and Rh-plating of the graphite furnace has been evaluated as a method of introducing the metallic form of Pd and Rh for chemical modification in electrothermal atomic absorption spectrometry. It is shown that by electroplating Pd and Rh onto the inner surface of the tube, the pretreated graphite surface may resemble the behaviour of the corresponding modifier. The resulting metallic layer is very effective in inhibiting the loss of volatile elements (e.g., As and Se), as well as reducing the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

1997
1997
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 19 publications
0
29
0
3
Order By: Relevance
“…[13][14][15][16] This probability was also investigated using sodium azide, NaN 3 as a reducing reagent. Under conditions optimized in the presence of 10 µg Pd (ashing, 500˚C; atomization, 1500˚C), the effect of different amounts of sodium azide on the absorbance of cadmium was investigated.…”
Section: Amount Of Matrix Modifier Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] This probability was also investigated using sodium azide, NaN 3 as a reducing reagent. Under conditions optimized in the presence of 10 µg Pd (ashing, 500˚C; atomization, 1500˚C), the effect of different amounts of sodium azide on the absorbance of cadmium was investigated.…”
Section: Amount Of Matrix Modifier Componentsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Recent studies have indicated that the stability effect of palladium for volatile elements is concerned with its metallic form. 9,[13][14][15][16] Therefore, palladium as a modifier is commonly used under reducing conditions. Palladium has been used with several reducing agents together, such as hydrazine, hydroxyl ammin hydrochloride and ascorbic acid.…”
mentioning
confidence: 99%
“…In such case, the modifier is introduced prior to the analysis by thermodeposition, electrodeposition or sputtering processes [9][10][11] and persists in the atomizer for numerous atomization cycles. For elements such as Pb, the modifying capability of Ir may last beyond 1100 firing cycles, even in the presence of complex matrices such as urine and blood, if the proper coating temperature program is used.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, graphite-furnace atomic absorption spectrometry (GFAAS) was also applied using different chemical matrix modifiers for the determination of a low level of mercury with higher sensitivity and a lower detection limit with various matrix modifiers, [14][15][16] especially when the mercury vapor had been concentrated in the graphite furnace with palladium and palladium-rhodium as an absorbent and matrix modifiers. 16,17 However, the instrumentation and chemical reagent of the GFAAS technique are often expensive.…”
Section: Introductionmentioning
confidence: 99%